2023
DOI: 10.15381/rivep.v34i1.23066
|View full text |Cite
|
Sign up to set email alerts
|

Detección molecular de Brucella sp, Leptospira spp y Toxoplasma gondii en felinos domésticos y silvestres y el impacto zoonótico en el personal encargado de su manejo en Pereira, Colombia

Abstract: El estudio buscó determinar la presencia de los agentes infecciosos causantes de la toxoplasmosis, brucelosis y leptospirosis empleando la técnica molecular PCR convencional en felinos domésticos y silvestres, así como en el personal relacionado con el cuidado y manejo de estos animales en la ciudad de Pereira, Risaralda (Colombia). Se tomaron muestras de sangre de felinos domésticos (n=99) y silvestres en cautiverio (n=4) y del personal responsable de su cuidado y manejo (médicos veterinarios, zootecnistas, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The sensitivity in blood samples decreases to 50% in the first five days of illness. Therefore, in future studies, it is suggested that PCR be conducted on urine samples, or both blood and urine should be analysed to improve diagnostic sensitivity (Lau et al, 2017), even using PCR variations that increase the specificity of the diagnosis (Caballero et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity in blood samples decreases to 50% in the first five days of illness. Therefore, in future studies, it is suggested that PCR be conducted on urine samples, or both blood and urine should be analysed to improve diagnostic sensitivity (Lau et al, 2017), even using PCR variations that increase the specificity of the diagnosis (Caballero et al, 2023).…”
Section: Resultsmentioning
confidence: 99%